The Obstacles to Macroeconomic Stabilization and a Keynesian-Institutionalist Agenda to the Brazilian Economy - Ferrari Filho, Fernando (Brazilian Keynesian Review, 2015)
The article aims at, on the one hand, arguing that the macroeconomic policies adopted since the Real Plan have not been able to ensure a sustainable economic growth and solve the main economic problems, such as balance of payments imbalances and structural bottlenecks. On the other hand, in the light of the Keynesian and Institutionalist approaches, it presents some economic measures to ensure macroeconomic stability, that is, sustainable economic growth, inflation under control, fiscal and external balances and income distribution.